Feasibility Study of Reusing Tarp Banners in the Furniture Production - Nejeliski, Danieli Maehler; Palhano, Ana Paula; Matoso, Lucas Gabriel (Sustainability in Debate, 2017)
Vinyl tarp is a low-budget material with good print quality, being widely used for making banners for advertising campaigns and academic events. In both applications, it quickly turns into waste. In this context, a research project was designed with the objective of studying the feasibility of reusing tarp banners in the furniture production. The project was developed with students of the Technical Course in Furniture of the Federal Institute Farroupilha (IFFar), Santa Rosa Campus. In the first stage, tests on cutting, joining, finishing and deforming were performed. The cutting of the material was considered feasible. The bonding with adhesives was unsatisfactory, with best results with mechanical bonding with metallic clips. Regarding the finish, paints were not able to cover homogeneously the surface. As for the resistance, the vinyl tarp underwent plastic deformation with the application of localized load. With restrictions, use of the material for production of furniture was considered viable. In the second stage, the design and prototype of column luminaires, coffee tables, folding benches and stackable niches were developed. The design of products prioritized the reuse and rational use of raw materials, a simplified production process and a contemporary aesthetic, consistent with the precepts of Ecodesign and economic viability.